Lehrermotivation - ein vernachlässigtes Thema in der empirischen Forschung - Müller, Florian H. (Array, 2008)
In the last decades many studies focused on conditions and effects of students’ learning motivation. In contrast teachers’ motivation and its relevance for students’ learning and classroom instruction is a largely neglected issue in educational research as well as in educational psychology. The paper investigates conditions of teachers’ motivation and the correlation of teachers’ motivation, classroom instruction and students’ learning motivation. Deci and Ryan’ s (2002) self-determination theory (SDT) provides the theoretical foundation for this study. It allows a differentiated analysis of the qualities of motivation (intrinsic motivation and four types of extrinsic motivation) and suggests that motivational processes are highly influenced by basic psychological needs for autonomy, competence and social relatedness. The results of the study show that institutional conditions of each school and the entire school system are interrelated with the self-determined motivation of teachers. The teacher’ s self-determined motivation is directly and in-directly associated with students’ self-determined learning motivation and with their need satisfaction in the classroom.